Human LYPD8 protein inhibits motility of flagellated bacteria - Chiao-Ching Hsu; Ryu Okumura; Kiyoshi Takeda (BMC, 2017)
Abstract Background We previously reported that the mouse Ly6/Plaur domain containing 8 (mLypd8), a GPI-anchored protein highly and selectively expressed on colonic epithelia, contributes to segregation of intestinal microbiota and intestinal epithelia and is critical for prevention of intestinal inflammation. In addition, it was found that human LYPD8 (hLYPD8) is expressed in the colonic epithelia and expression of hLYPD8 is reduced in some ulcerative colitis patients. However, the molecular characteristics and functions of hLYPD8 remain unclear. In this study, we generated the hLYPD8 protein and characterized its functions. Methods To analyze the characteristics and functions of the hLYPD8 protein, recombinant FLAG-tagged hLYPD8 protein was generated by two kinds of protein expression systems: a mammalian cell expression system and a Pichia pastoris expression system. Recombinant hLYPD8 protein was analyzed by western blot analysis or deglycosylation assay. The effect of the protein on flagellated bacteria was examined by ELISA assay and motility assay using semi-agar plates. Results hLYPD8 was a highly N-glycosylated GPI-anchored protein, like mLypd8. Moreover, recombinant hLYPD8 protein generated by the Pichia pastoris expression system using the SuperMan5 strain, which enabled production of a large number of proteins with human-like glycosylation, presented the high binding affinity and the motility inhibitory function to flagellated bacteria, such as Proteus mirabilis. Conclusions These results demonstrated that hLYPD8 inhibits the motile activity of flagellated bacteria, many of which are involved in intestinal inflammation. The supplementation of recombinant hLYPD8 protein might be a novel therapeutic approach for intestinal inflammation of inflammatory bowel diseases.